2021
DOI: 10.3390/genes12101614
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulatory Dynamics in Models of Methamphetamine-Use Disorder

Abstract: Methamphetamine (METH)-use disorder (MUD) is a very serious, potentially lethal, biopsychosocial disease. Exposure to METH causes long-term changes to brain regions involved in reward processing and motivation, leading vulnerable individuals to engage in pathological drug-seeking and drug-taking behavior that can remain a lifelong struggle. It is crucial to elucidate underlying mechanisms by which exposure to METH leads to molecular neuroadaptive changes at transcriptional and translational levels. Changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 141 publications
(197 reference statements)
2
12
0
Order By: Relevance
“…2f, g). This finding provides evidence that complicated epigenetic remodeling events at different levels can be induced by METH exposure, as previous studies have reported [1, 3, 19, 24, 27, 33, 45].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…2f, g). This finding provides evidence that complicated epigenetic remodeling events at different levels can be induced by METH exposure, as previous studies have reported [1, 3, 19, 24, 27, 33, 45].…”
Section: Discussionsupporting
confidence: 85%
“…Methamphetamine (METH) is a stimulant amphetamine drug that is extremely persistently addictive, with 61% of individuals treated for METH use disorder relapsing within one year [16-18]. Recently, developed animal models, especially rodent models, helped us better understand the molecular consequences of substance abuse [1, 23, 27]. Although previous studies illustrated that METH exposure could cause dramatic epigenetic changes in the NAc and frontal cortex [1, 3, 27, 33, 44], there is still a lack of a clear description of the molecular changes in different brain regions under METH exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of DNA sequencing information does not change throughout life; however, the manipulation of gene expression is possibly mediated by the chemical modification of DNA itself or by DNA-binding proteins such as histone [30][31][32][33][34][35] (Figure 1A). This epigenetic modification can alter the function of the skin, and it is possible for the skin to adapt to these environmental changes [16,36].…”
Section: Epigenetic Modificationmentioning
confidence: 99%